Crisis of transcendence : a theology of digital art and culture - Elwell, J. Sage, 1975- (Lanham, MD : Lexington Books, 2010)
From the Internet to the iPhone, digital technology is no mere cultural artifact. It affects how we experience and understand our world and ourselves at the deepest levels-it is a fundamental condition of living. The digitization of modern life constitutes an essential field of religious concern because it impacts our individual and cultural sensibilities so profoundly. Despite this, it has yet to be thematized as the subject of religious or theological reflection. The Crisis of Transcendence remedies this by asking a single significant question: How is digital technology impacting the moral a.
Fetish : biological art and the death of God -- Prosthetic : database art and the death of the subject -- Fragment : Internet art and the crisis of transcendence -- Bricolage : intermedia art and the integrity of fallibility.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Christianity and art; Computer art; Christianity and culture; Technology -- Religious aspects -- Christianity; RELIGION -- Christianity -- General; Christianity and art; Christianity and culture; Computer art; Technology -- Religious aspects -- Christianity; Electronic books